2010
DOI: 10.1002/app.33346
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of nylon 6 films treated with an He/O2 atmospheric pressure plasma jet

Abstract: To investigate the effect of the gas composition of the plasma treatment on the surface modification of an atmospheric pressure plasma jet (APPJ), nylon 6 films were treated with APPJ with pure helium (He), He þ 1% oxygen (O 2 ), and He þ 2% O 2 , respectively. Atomic force microscopy showed increased surface roughness, whereas X-ray photoelectron spectroscopy revealed increased oxygen contents after the plasma treatments. The plasma-treated samples had lower water contact angles and higher T-peel strengths th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Etching is one of the ways in which the plasma treatment acts upon the material; during this process the surface of the material is bombarded with plasma. This action causes the values of the dispersive component (γ S d ) of the surface energy to increase, thereby increasing the hydrophilic nature of the ionomer surface [26–29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Etching is one of the ways in which the plasma treatment acts upon the material; during this process the surface of the material is bombarded with plasma. This action causes the values of the dispersive component (γ S d ) of the surface energy to increase, thereby increasing the hydrophilic nature of the ionomer surface [26–29].…”
Section: Resultsmentioning
confidence: 99%
“…The action of the plasma produces oxidation of the surface species of the sample which increase its polarity; however, in this case the ionomer sample already contains some oxygen and therefore new chemical species are not created. Instead the quantity of compounds containing oxygen will increase resulting in an increase in the peaks associated with said compounds [27, 30].…”
Section: Resultsmentioning
confidence: 99%
“…However, the discharge is generated in helium (other gases are used with helium), which on commercial scale becomes expensive, unless helium is substantially recovered. The atmospheric-pressure He and He + O 2 plasma treated nylon 6 films showed increased surface roughnesses, increased surface oxygen contents, and hydrophilic polar groups; this led to lower water contact angles and improved bonding strength (Gao et al, 2011). They have further observed that, when the amount of oxygen increased from 1 to 2% in the plasma-gas mixture, all of these favorable effects were further enhanced.…”
Section: Atmospheric Pressure Plasmasmentioning
confidence: 91%
“…Although the fibers possess excellent mechanical, chemical, and thermal properties, there are still some limitations on its uses and applications [1][2][3][4][5][6][7][8][9][10]. In general, to extend the use and applications of polymers, several treatments are employed and some of them uses atmospheric pressure plasma to improve the dye uptake of nylon 6 fibers with different absorbed moisture [1] and to enhance the antibacterial activity and natural dyeing properties of nylon 6 fabrics [6]; direct low-pressure and low-temperature plasma to enhance the adhesion of carbon nanotubes on nylon 6,6 fabrics [3], to improve the mechanical properties of nylon 6 plain woven fabrics [5], to correlate the crystallinity and plasma susceptibility of poly(ethylene terephthalate) (PET) and nylon 6,6 fibers [10], and to achieve superhydrophilic or superhydrophobic properties for lignocellulosic seagrass, PET, and poly(tetrafluoroethylene) (PTFE) materials [11][12][13][14]; gas discharges in improving the wettability, superhydrophobicity and antibacterial properties of PTFE [15][16][17][18]; laser to improve the dyeability of poly(amide) 6,6 knitted fabrics [19]; and microwave jet plasma for the functionalization of electrospun poly(amide) 6 nanofibers to improve the adhesion properties during the production of composites in tissue engineering [7].…”
Section: Introductionmentioning
confidence: 99%